Correlates of antiretroviral therapy (ART) initiation among HIV-positive men who have sex with men (MSM) in China - Liying Wang; Chenglin Hong; Jane M. Simoni; Na He; Chenxing Li; Lingxiao Chen; Frank Wong (Inishmore Laser Scientific Publishing Ltd, 2022)
# Background Men who have sex with men (MSM) are disproportionately affected by HIV globally and in China. Early antiretroviral therapy (ART) can reduce HIV-related illness, improve quality of life, and decrease HIV incidence rates. Given the high vulnerability of and limited research on ART coverage in China, we describe the ART initiation rate and correlates of ART initiation using Anderson's health service utilization model. # Methods We conducted a cross-sectional survey and collected blood samples for HIV and HCV testing and CD4 count among MSM recruited in Chengdu and Shanghai, China (N= 1,633). Using stepwise logistic regression, we explored factors associated with ART initiation postulated by Anderson's health service utilization model. # Results More than half of the participants had not started ART (53.5%). Older age and Han ethnicity were associated with a higher probability of ART initiation. Being married, higher monthly income (> US$464.35), retirement, depression, and condomless anal sex predicted a lower probability of ART initiation. # Conclusions The ART initiation rate among MSM in this study is lower than the national level of ART coverage among all people living with HIV (PLWH) in China. ART initiation is best predicted by demographic characteristics such as age and ethnicity. Participants who are retired, married, reported depressive symptoms, and sexual risk behavior are less likely to have initiated ART. Future studies could examine whether integrating mental health and sexual health services into the current HIV care continuum is beneficial to ART initiation among MSM. Strategies should be developed to promote ART initiation among certain populations such as young MSM and ethnic minorities in China.